2022
DOI: 10.1039/d2tb00291d
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic shell nanomagnetic adsorbents for selective and highly efficient capture of low-density lipoprotein from hyperlipidaemia serum

Abstract: Removal of low-density lipoprotein (LDL) from hyperlipemia patients’ blood represents an effective approach to prevent the progression of atherosclerotic cardiovascular disease. Based on the LDL structural characteristics and intermolecular interactions,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The electropositivity of LDL is attributed to the presence of arginine and lysine clusters at the 25% position of the carboxyl terminus of apoB-100 . In addition, the presence of a large number of UC and lipophilic moieties on apoB-100 endows LDL with fairly strong hydrophobicity so that both hydrophobic and electrostatic domains are present on the surface of LDL. , On the contrary, the major proprotein domain of HDL, apolipoprotein A-I (apoA-I), demonstrated an electrically neutral property due to the equal numbers of positively and negatively charged amino acid residues. , Therefore, the nanoadsorbent was designed to possess both negatively charged moieties and hydrophobic groups to facilitate the binding with LDL and repulsion of DHL during the adsorption process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electropositivity of LDL is attributed to the presence of arginine and lysine clusters at the 25% position of the carboxyl terminus of apoB-100 . In addition, the presence of a large number of UC and lipophilic moieties on apoB-100 endows LDL with fairly strong hydrophobicity so that both hydrophobic and electrostatic domains are present on the surface of LDL. , On the contrary, the major proprotein domain of HDL, apolipoprotein A-I (apoA-I), demonstrated an electrically neutral property due to the equal numbers of positively and negatively charged amino acid residues. , Therefore, the nanoadsorbent was designed to possess both negatively charged moieties and hydrophobic groups to facilitate the binding with LDL and repulsion of DHL during the adsorption process.…”
Section: Resultsmentioning
confidence: 99%
“…39,40 On the contrary, the major proprotein domain of HDL, apolipoprotein A-I (apoA-I), demonstrated an electrically neutral property due to the equal numbers of positively and negatively charged amino acid residues. 41,42 Therefore, the nanoadsorbent was designed to possess both negatively charged moieties and hydrophobic groups to facilitate the binding with LDL and repulsion of DHL during the adsorption process.…”
Section: Adsorption Experimentmentioning
confidence: 99%
“…In this study, a simple and convenient method of PDIC is employed for the preparation of microspheres, allowing for the production of a large quantity of microspheres within 3 min. , Rosiglitazone (R), a selective peroxisome proliferator-activated receptor gamma agonist, is chosen as a typical drug to inhibit the inflammatory response in AS. Acrylic acid (AA) and acrylated chondroitin sodium sulfate (CSA) are used to provide negatively charged sites for LDL adsorption due to their abundant carboxyl and sulfonic acid groups, and the CSA (structure similar to LDL receptors) has been shown to recognize LDL to some extent. ,, Acrylated beta-cyclodextrin (CD) with a hydrophilic outer cavity and hydrophobic inner cavity is utilized as a weak binding site for R and provides a strong hydrophobic site for LDL after R release. , In brief, monomers are dissolved in deionized water to obtain homogeneous aqueous solution, and then, AA-CSA-CD are prepared through the PDIC in a single droplet. The obtained microspheres are placed in a dimethyl sulfoxide solution of R, and after complete binding of the R, the LDL adsorption microspheres AA-CSA-CD-R are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…acute coronary syndrome [ 10 ], muscle weakness [ 11 ], muscle pain [ 12 ] and low efficacy) from existing treatments and inefficacy in managing patients with LDL levels above 300 mg/dl [ 13 ] pose significant obstacles to HLP treatment. Studies have indicated that selectively lowering LDL level while maintaining HDL with anti-atherosclerotic properties in patients represents a promising clinical treatment strategy for HLP [ 14 , 15 ]. Encouragingly, hemopurification-based adsorption has shown to be an effective therapy for treating HLP, demonstrating not only good adsorption efficiency for pathogenic LDL and selectivity adsorption resisting HDL, but also a reduction in toxicities, particularly effective for patients with familial hypercholesterolemia [ 16 ] and those who fail to achieve complete recovery through diet and drug therapy.…”
Section: Introductionmentioning
confidence: 99%